2019
DOI: 10.3991/ijet.v14i04.9363
|View full text |Cite
|
Sign up to set email alerts
|

Facebook as a Platform of Social Interactions for Meaningful Learning

Abstract: Undeniably, Facebook has become a significant part of students’ life in the 21st century. Therefore, interactions between instructors and students play a major role in learning through an online social learning environment like Facebook. Such an interaction is known as the key elements that can measure students’ learning process, particularly in an online learning environment. Past researchers have agreed that a social networking site does not only promote social interaction but also have high potential to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
(44 reference statements)
0
17
0
2
Order By: Relevance
“…Therefore, this study implies that consideration to integrate informal learning activities in formal instructional settings should be taken into account [27]. For example, encouraging online activities between students and teacher through Facebook using appropriate interactions design to make learning more fun and meaningful [28], especially EFL learning activities. It is a potential application for both teaching and learning [29].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this study implies that consideration to integrate informal learning activities in formal instructional settings should be taken into account [27]. For example, encouraging online activities between students and teacher through Facebook using appropriate interactions design to make learning more fun and meaningful [28], especially EFL learning activities. It is a potential application for both teaching and learning [29].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been found that there are some gender differences in the use of social networks. On average, women spend more time on social networks, create more independent content, and share it more often [14], [29], [25]. This feature can be observed in the early school years if children at this age already have access to communication technologies [30].…”
Section: Discussionmentioning
confidence: 99%
“…On average, women spend more time on social networks, create more independent content, and share it more often [14], [29], [25]. This feature can be observed in the early school years if children at this age already have access to communication technologies [30]. Three key factors in the use of social networks have been identified: the consumption of content (including content determination, search and selection), content sharing and content creation.…”
Section: Discussionmentioning
confidence: 99%
“…La perspectiva cognitivista (Piaget, 1962(Piaget, , 1968(Piaget, , 1973(Piaget, , 1986, se asume desde la mirada de Piaget, comprendido mediante la acomodación de una estructura de conocimiento para generar nueva información apropiada. El constructivismo recoge, de una parte, el concepto de Piaget referente a la interacción con los objetos de conocimiento; por otra parte, Vygotsky se plantea de la interacción con los otros; y distintos autores indican la importancia de la interacción significativa (Jumaat et al, 2019;Riestenberg, 2020;Shin, Kim, & Song, 2020). Así que el tutor debe hacer una relación entre lo pedagógico, lo comunicativo y la mediación en línea, a fin de construir un balance (Vygotsky, 2013).…”
Section: Coyuntura Y Quehacer Docenteunclassified